Interatrial Septum Myxoma - Rodrigues, H (2005)
The authors describe a case of a 55 years male, with class II cardiac insufficiency, with a mass in left atrium detected by echocardiography. MR showed a mass with 4cm arising from the interatrial septum, with similar intensity to myocardium on T1, high intensity T2, and intense enhancement after gadolinium.